Skazane na zapomnienie — prawo handlowe w PRL - Kułak, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The post-war history of Polish commercial law is not a frequent subject of interest in the literature. Historical reflection is usually limited to indicating that the civil code entering into force on 1 January 1965 and, on the same day, the repeal of the pre-war commercial code from 1934 formally ended the era of Polish private law’s duality — the coexistence of two equal branches of law: civil law, regulating common relations, and commercial law, regulating economic relations. However, it was the last symbolic chord in the history of commercial law during the communist period. In fact, it had been extinguished several years earlier and replaced by a socialist substitute in the form of economic law, intended to regulate the centrally planned, socialist trading, in which there was no space for individual economic activity. The article discusses the mechanism of dismantling commercial law in the political and economical order of the totalitarian state, which Poland became after the Second World War. This mechanism was implemented not on the normative level, by repealing the norms of commercial law, but on the factual one, by eliminating — through administrative, fiscal, and penal pressure methods — addressees of commercial law (already existing and potential entrepreneurs) and taking them away, e.g. by nationalizing the most essential components of their enterprises. In this way, the necessary (personal and property) background of commercial law was destroyed, making its norms irrelevant. Thus, commercial law was condemned to a dozen or so years of non-existence and oblivion before the legislator decided to make a formal decision, which was to repeal most provisions of the commercial code. Only those regulations remained in force that were needed by the communist authorities, e.g. to conduct foreign trade. The effects of several-decades-long systemic non-existence of commercial law are still noticeable today. Despite the systemic transformation in 1989 and the return of the Polish economy to free market rules, Polish commercial law — relegated to the role of a specialized discipline of civil law and formally distinguished only for research and teaching activities — has not yet regained its rank as an independent branch of private law.
Keywords: prawo handlowe; kodeks handlowy; kodeks cywilny; jedność prawa prywatnego; gospodarka; PRL